Pemberdayaan Masyarakat Dalam Rangka Pencegahan Stunting Sejak Dini di Kecamatan Pagedongan Kabupaten Banjarnegara - Hidayatu Munawaroh; Moh Syakur; Nur Fitriana; Rifqi Muntaqo (LP2M of Institute for Research and Community Services - UIN Walisongo, 2020)
This study examines the problem most basic health problem for children in Indonesia today is in their growth and development, in other words, it is a problem of stunting. The government has made various efforts to prevent stunting, one of which is specifically intervening in child nutrition. In order to support government programs, we carry out a community service activity with the aim of detecting and detecting children's nutritional development. The Banjarnegara City Government has detected that 29% of children are still affected by stunting. By involving local health workers totaling 35 cadres in these activities. In the process of implementing the activity, it is divided into 3 terms in one day, while the methods used are counseling, discussion and practice. Based on the results of the activity, the cadres experienced an increase in quality. Previously, knowledge of health cadres was only in the range of 37.14%, but after participating in the activity, there was a significant increase of 80%. Likewise, there was an increase (p = 0.000; α 0.05) since this intervention. The recommendation is that there should be activities like this on an ongoing basis and if necessary, early detection of stunting. Penelitian ini mengkaji permasalahan kesehatan pada anak di Indonesia yang paling mendasar saat ini adalah pada pertumbuhan dan perkembangannya, dengan kata lain ini adalah masalah stunting. Pemerintah telah melakukan berbagai upaya dalam menangani stunting ini, salah satunya mengintervensi gizi anak secara spesifik. Dalam rangka mendukung program pemerintah, kami melakukan suatu kegiatan pengabdian masyarakat dengan tujuan mendeteksi sekaligus mendeteksi perkembangan gizi anak. Pemerintah Kota Banjarnegara mendeteksi adanya 29 % anak masih terdampak stunting. Dengan melibatkan tenaga kesehatan setempat berjumlah 35 kader dalam kegiatan tersebut. Pada proses pelaksanaan kegiatan terbagi menjadi 3 termin dalam satu hari, adapun metode yang digunakan yakni penyuluhan, diskusi dan praktek. Berdasarkan hasil kegiatan, kader mengalami peningkatan kualitas. Sebelumnya pengetahuan tenaga kesehatan hanya pada kisaran 37,14%, namun setelah mengikuti kegiatan mengalami peningkatan yang signifikan 80%. Begitu juga, terjadi peningkatan (p = 0,000; α 0,05) semenjak adanya intervensi ini. Rekomendasinya adalah perlu adanya kegiatan seperti ini secara berkelanjutan dan bila perlu adanya pendeteksian stunting sejak dini.